Dupilumab treatment is not associated with changes in lymphoma risk in atopic dermatitis and other type 2 inflammatory diseases: data from a large-scale retrospective cohort study - Kridin, Khalaf; Bieber, Katja; Olbrich, Henning; von Bubnoff, Dagmar; Hernandez, Gema; Zirpel, Henner; von Bubnoff, Nikolas; Thaçi, Diamant; Ludwig, Ralf J. (Frontiers in Medicine, 2026)
BackgroundThe association between atopic dermatitis (AD) and lymphoma risk remains inconclusive. Dupilumab, approved for moderate-to-severe AD, has been linked to an increased lymphoma risk, raising significant concerns.ObjectivesThe objective of the study was to clarify the association between AD and lymphoma risk and extend to non-dermatological type 2 inflammatory diseases (T2IDs). This study also aimed to assess the impact of dupilumab on lymphoma risk in AD and non-dermatological T2IDs.MethodsA retrospective cohort study was conducted using the TriNetX database. Propensity-score matching allowed for better comparability, and sensitivity analyses ensured robustness.ResultsAmong 801,508 cases and controls, AD was associated with an increased risk of lymphoma, e.g., cutaneous T-cell lymphoma (CTCL) and non-Hodgkin lymphoma (NHL). Among 14.4 million cases and controls, non-dermatological T2IDs also conferred an increased lymphoma risk. In the comparison of AD patients treated with dupilumab versus other systemic treatments (n = 7,840 per group), dupilumab exposure did not alter the risk for lymphomas but tended toward reduced risks. This decreased risk association was most evident in non-dermatological T2IDs (n = 16,908 per group).LimitationsRetrospective data analysis, data quality, possible false registration of ICD-10-codes.ConclusionT2IDs, including AD, are associated with a significantly increased risk for lymphoma. Treatment with dupilumab partially ameliorates this risk association, especially for NHL.